Distribution and drivers of costs in type 2 diabetes mellitus treated with oral hypoglycemic agents: a retrospective claims data analysis. (September 2014) - Bron, Morgan; Guerin, Annie; Latremouille-Viau, Dominick; Ionescu-Ittu, Raluca; Viswanathan, Prabhakar; Lopez, Claudia; Wu, Eric Q.
Abstract Objective: To describe the distribution of costs and to identify the drivers of high costs among adult patients with type 2 diabetes mellitus (T2DM) receiving oral hypoglycemic agents. Methods: T2DM patients using oral hypoglycemic agents and having HbA1c test data were identified from the Truven MarketScan databases of Commercial and Medicare Supplemental insurance claims (2004–2010). All-cause and diabetes-related annual direct healthcare costs were measured and reported by cost components. The 25% most costly patients in the study sample were defined as high-cost patients. Drivers of high costs were identified in multivariate logistic regressions. Results: Total 1-year all-cause costs for the 4104 study patients were $55, 599, 311 (mean cost per patient = $13, 548). Diabetes-related costs accounted for 33.8% of all-cause costs (mean cost per patient = $4583). Medical service costs accounted for the majority of all-cause and diabetes-related total costs (63.7% and 59.5%, respectively), with a minority of patients incurring >80% of these costs (23.5% and 14.7%, respectively). Within the medical claims, inpatient admission for diabetes-complications was the strongest cost driver for both all-cause (OR = 13.5, 95% CI = 8.1–23.6) and diabetes-related costs (OR = 9.7, 95% CI = 6.3–15.1), with macrovascular complications accounting for most inpatient admissions. Other cost drivers included heavier hypoglycemic agent use, diabetes complications, and chronic diseases. Limitations: The study reports a conservative estimate for the relative share of diabetes-related costs relative to total cost. The findings of this study apply mainly to T2DM patients under 65 years of age. Conclusions: Among the T2DM patients receiving oral hypoglycemic agents, 23.5% of patients incurred 80% of the all-cause healthcare costs, with these costs being driven by inpatient admissions, complications of diabetes, and chronic diseases. Interventions targeting inpatient admissions and/or complications of diabetes may contribute to the decrease of the diabetes economic burden.